Holocene history of Ria Formosa coastal lagoon system (Southern Portugal): borehole evidence and threedimensional paleotopography - Mendes da Silva de Sousa, Carlos A (2013)
A paleotopographic model of Ria Formosa is presented based on two borehole campaigns and a systematic comparison with previous works, revealing the existence of a complex network of fluvial valleys. Vertical sediment profiles showed a mosaic of changing depositional environments, resulting from local hydrodynamics, sedimentary sources and, to an extent, by the structurally inherited accommodation space. Sedimentological, geochemical and micropaleontological data were put in the context of an age model obtained from 14C datings, pointing to the existence of an estuarine environment subjected to a rapid coastal flooding from ca. 10000 to 7500 cal. years B.P., followed by a period of infilling in an increasingly confined coastal lagoon environment.